Wstępne podsumowanie badań zaburzeń mowy u dzieci w wieku przedszkolnym z dysfunkcją fazy połykania i oddychania - Malicka, Izabela (Logopedia Silesiana, 2014)
Preliminary summary of researches dealing with disorders of speech regarding childrenof pre-school age with the dysfunction of swallowing and breathingIn the article the author presents the results of initial research of disorders of the oralphase of swallowing and breathing in children of preschool age. She points out the relationshipbetween breathing, swallowing and the development of child’s phonetic and phonological system.The aim is to identify the existing difficulties of the patient to plan speech-therapy with the focus onachieving proper articulation.